PENDEKATAN TEORI KOGNITIF DALAM PSIKOLOGI PENDIDIKAN ISLAM ANAK: ANALISIS KONSEPTUAL DAN IMPLIKASI PEMBELAJARAN MODERN - Amalia Nurusyabani; Muhammad Zainurrahman; Lezya Oliviana (LPPM IAD Probolinggo, 2026)
This study explores the integration of cognitive theory into Islamic educational psychology as a conceptual and practical response to the challenges of modern learning. Using a qualitative library research method, this paper analyzes how Piaget’s cognitive theory and Islamic perspectives on cognition can be harmonized to create a holistic model of learning that balances intellectual and spiritual development. The study identifies that cognitive processes in Islamic education should not only focus on reasoning and conceptual understanding but also embed spiritual values such as tawhid, ikhlas, and amanah as intrinsic parts of learning. The findings reveal that the integration of Islamic values into cognitive paradigms strengthens critical thinking, metacognition, and moral awareness. Furthermore, the constructivist approach combined with Islamic spirituality encourages students to construct knowledge meaningfully while maintaining ethical consciousness. The paper concludes that the synergy between reason (‘aql) and revelation (wahy) forms the foundation of Islamic educational psychology, offering theoretical and practical implications for curriculum design, teacher training, and educational policy. This integrative model emphasizes that knowledge is both an intellectual pursuit and a spiritual journey toward understanding divine truth.